“Don’t Make Me Feel Dumb”: Transfer Students, the Library, and Acclimating to a New Campus - Harrick, Matthew; Fullington, Lee Ann (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2019)
Objective – This qualitative study sought to delineate and understand the role of the library in addressing the barriers transfer students experience upon acclimating to their new campus.Methods – A screening survey was used to recruit transfer students in their first semester at Brooklyn College (BC) to participate in focus groups. The participants discussed the issues they encountered by answering open-ended questions about their experiences on campus, and with the library specifically.Results – Transfer students desired current information about campus procedures, services, and academic support. They often had to find this information on their own, wasting valuable time. Students felt confused and stressed by this process; however, strategic library involvement can help alleviate this stress.Conclusion – Involving the library more fully in orientations could ease students’ confusion in their transitional semester. Students desired local knowledge, and the library is in a key position to disseminate this information.